2017
DOI: 10.32677/ijch.2017.v04.i03.017
|View full text |Cite
|
Sign up to set email alerts
|

A study on nutritional status of Anganwadi children in a rural area of North Kerala

Abstract: Background: Malnutrition being the biggest contributor to child mortality and morbidity is highly prevalent among preschool children in India. The state of Kerala which tops the list in most of the health indicators in India is no exception to wide prevalence of malnutrition in children. Objective: To assess the nutritional status of Anganwadi children aged 2-5 years in a rural area of North Kerala. Materials and Methods: A cross-sectional study was done among Anganwadi children between 2 and 5 years of age fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
0
5
1
Order By: Relevance
“…In different studies conducted by Sukla P et al [20] at Chhattisgarh, Singh H et al [26] in tribal district of Kinnaur in Himachal Pradesh and Chakravarthy KB et al (2015) [27] in Andhra Pradesh found the prevalence rate of stunting between 27.40% to 35.50% which were similar to the present study. In another study done by Radhamani KV et al [23] found the prevalence rate of stunting as 10.60% which is very low when compared to the present study. The reason for higher prevalence of stunting in the present study may be because of poor diet intake and repeated infections among the children.…”
Section: Original Research Articlecontrasting
confidence: 72%
See 2 more Smart Citations
“…In different studies conducted by Sukla P et al [20] at Chhattisgarh, Singh H et al [26] in tribal district of Kinnaur in Himachal Pradesh and Chakravarthy KB et al (2015) [27] in Andhra Pradesh found the prevalence rate of stunting between 27.40% to 35.50% which were similar to the present study. In another study done by Radhamani KV et al [23] found the prevalence rate of stunting as 10.60% which is very low when compared to the present study. The reason for higher prevalence of stunting in the present study may be because of poor diet intake and repeated infections among the children.…”
Section: Original Research Articlecontrasting
confidence: 72%
“…Similar findings were observed by other studies conducted by Sukla P et al [20] at Chhattisgarh, Mamulwar MS et al [21] in Pune and Islam S et al [22] in a tribal area of Dibrugarh district of Assam which found the prevalence rate of underweight between 29.00% to 36.00% respectively. While in contrast, the study done by Radhamani KV et al [23] showed the prevalence rate of underweight as 14.60% at North Kerala. The higher prevalence of underweight in the present study could be due to low literacy level of the mothers.…”
Section: Original Research Articlementioning
confidence: 83%
See 1 more Smart Citation
“…In our study girls found to be more in number compared to boys similar to the study done by Radhamani et al The majority of children were falling in age group 3-4 yrs. 6 In the present study mothers who were illiterate and unemployed, who had children suffering from under nutrition and also were falling in class-4 and class-5. 7 According to BG Prasad classification which is significant in relation to Under Nutrition with p<0.05.…”
Section: Discussionmentioning
confidence: 59%
“…In India, according to the findings of Hunger and Malnutrition survey by Anonymous (2012) in 112 districts across nine states of the country has revealed that 42.3% children under the age of five years are underweight, 58.8% are stunted and 11.4 % are wasted. Radhamani and Rajeev (2017) reported that underweight, stunting, and wasting were most prevalent in 2-3-yearoldchildren and minimum among 3-4-year-old children. Elizabeth (2010) reported that nutritional problems among children cause major morbidity and mortality in India.…”
Section: Introductionmentioning
confidence: 99%